2012
DOI: 10.1673/031.012.7901
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Variations in the Grasshopper,Chromacris speciosafrom Two Localities of Pernambuco in Northeastern Brazil

Abstract: The present study describes morphometric variations in the grasshopper, Chromacris speciosa (Thunberg, 1824) (Orthoptera: Acridoidea: Romaleidae) from two locations in the state of Pernambuco, Brazil. The distance between the sites chosen for collections (Recife and São Lourenço da Mata) is approximately 16 km. The investigation was based on a comparative study of external morphological characteristics of the grasshoppers. Morphometric measurements took into account the different body parts and appendages. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In addition to the structures suggested by Otte (1979) as diagnostic characters for identification of O. punctata, the present study showed that the head also presented intraspecific variation, reinforcing the needs for other structures to be used in the identification of this species. Intraspecific variations in the morphological characters, such as head, pronotum, femur, body, and wings, have also been reported in studies conducted on the populations of Chromacris speciosa (Thunberg) collected from two locations in Pernambuco, Brazil (Cisneiros et al 2012). Also, analyses of the body size and the wings of Trilophidia annulata (Thunberg) (Orthoptera: Oedipodinae) demonstrated significant differences among the populations collected from different kinds of environments in China (Bai et al 2016), which corroborates the occurrence of variations in individuals of the same species living in different biomes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition to the structures suggested by Otte (1979) as diagnostic characters for identification of O. punctata, the present study showed that the head also presented intraspecific variation, reinforcing the needs for other structures to be used in the identification of this species. Intraspecific variations in the morphological characters, such as head, pronotum, femur, body, and wings, have also been reported in studies conducted on the populations of Chromacris speciosa (Thunberg) collected from two locations in Pernambuco, Brazil (Cisneiros et al 2012). Also, analyses of the body size and the wings of Trilophidia annulata (Thunberg) (Orthoptera: Oedipodinae) demonstrated significant differences among the populations collected from different kinds of environments in China (Bai et al 2016), which corroborates the occurrence of variations in individuals of the same species living in different biomes.…”
Section: Discussionmentioning
confidence: 75%
“…Although geometric morphometrics has been demonstrated to be effective in analyzing morphological variation in insects, this methodology has been underused in studies of Orthoptera (Song and Wenzel 2008, Song 2009, Bidau et al 2012, Cisneiros et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…After each trial, males were placed in a freezer (-20°C) for 48h and preserved in 70% ethyl alcohol. Following [ 58 ] we measured femur and pronotum length using Vertex™ Vernier digital callipers (England, UK) to the nearest 0.01 mm. Femur length was taken from the trochanter to the beginning of the femur-tibia joint.…”
Section: Methodsmentioning
confidence: 99%
“…Grasshoppers (Orthoptera: Acrididae and Romaleidae) inflict serious damage to plants throughout their development (Franc & Luong-Skovmand 2009). These harmful species are polyphagous and feed voraciously on leaves of several agricultural important crops (coconut, açaí tree, cotton, sugarcane, pastures, etc.)…”
mentioning
confidence: 99%